Meningkatkan Hasil Belajar Peserta Didik Materi Penjumlahan dan Pengurangan Melalui Media Papan Jurang di Kelas II SD Maitreyawira Palembang - Mustika, Ayu; Noviyanti, Desi; Mulyono, Budi; Fauzie, Fauzie; Sellafeni, Angki Suci; X Santi, Eggah Sania; Rosada, Dika Amrina; Suandi, Aldi Tri (SJEE (Scientific Journals of Economic Education), 2025)
This research aims to improve student learning outcomes in mathematics subjects including addition and subtraction of whole numbers in class II D at Maitreyawira Elementary School, Palembang. This research is classroom action research that uses a PBL (Problem Based Learning) application model assisted by gap board media. Based on the results of research conducted through three cycles, it is stated that the application of the Problem Based Learning Model assisted by the Gorge Board media (Addition and subtraction) improves Mathematics learning outcomes in class IID students at Maitreyawira Elementary School. This can be seen from the average value of cognitive learning outcomes obtained by 29 students at Maitreyawira Elementary School in Palembang, the results of pre-cycle I, cycle II, cycle III and cycle IV tests always increase. Pre-cycle 5 students percentage 17% (Completed) and 24 students percentage 83% (Not Complete). With the problem of lack of student learning outcomes, the researcher applied the Problem Based Learning model assisted by the Gap Board media (Addition and subtraction) student learning outcomes increased in the second cycle, obtaining 19 students with a percentage of 66% (Completed) and 10 students with a percentage of 34% (Incomplete. In cycle III experienced an increase from cycle II with 20 students achieving a completeness percentage of 69% (Completed) and 9 students achieving a percentage of 31% (Not Completed. Meanwhile, in cycle IV reflection was carried out so that it experienced an increase from cycle III with a completeness achievement of 27 students with a percentage of 93%). (Completed) and 2 students with a percentage of 7% (Not Completed).